A QUESTIONNAIRE TO DETERMINE THE WORK MOTIVATION OF AGRICULTURAL EXTENSION WORKERS IN INDONESIA - Arissaryadin Arissaryadin; Yayuk Yuliati; Kliwon Hidayat; Edi Dwi Dwi Cahyono (Socio-Economics/Agribusiness Department, 2022)
A review of the literature reveals that most previous studies only used achievement motivation theory to assess the work motivation of agricultural extension workers in Indonesia. So far, no research questionnaire has been designed using expectancy theory. The purpose of this study is to develop a work motivation questionnaire based on expectancy theory and to test the convergent validity, discriminant validity, construct reliability and composite reliability of this questionnaire. This study drew on data from 107 people who work as agricultural extension workers in Indonesia. The questionnaire distributed via google forms was completed by all respondents. All statistical analyses were performed using JASP, version 0.16, and a confirmatory factor analysis technique was used. This study resulted in the development of a work motivation questionnaire in Indonesian. There are nine-item questions, each with three questions for construct expectancy, three questions for constructs instrumentality, and three questions for constructs valence. Confirmatory factor analysis confirmed that all of the question items from the expectancy theory three constructs met the convergent validity, discriminant validity, construct reliability, and composite reliability criteria. This questionnaire can be used in future research on agricultural extension workers' work motivation in Indonesia.